(untitled) (Herald of Journalism, 2020)
The article is devoted to the PR implementation of national programs of Kazakhstan. PR-support of the decisions of the state in sphere of national programs is one of the most important factors of sustainable development of the country. The participation of public relations in public administration can be described as assisting the government in the resolution of objective contradictions between the pluralism of the political sphere of society and the integrity of the government.